Constitutionalism: Concept and Application in the Federal and State Governments of Malaysia - Sabarudin, Johan S (Journal of Malaysian and Comparative Law, 2019)
This article seeks to briefly explore the meaning of constitutionalism in the constitutional system of Malaysia and how this is applied in both the Federal and State Governments.